A novel independent heat extraction-release double helix energy pile: Numerical and experimental investigations of heat extraction effect. (15th February 2022) - Huang, Guangqin; Liao, Ziming; Li, Shengbo; Zhuang, Chunlong; Zhang, Hongyu; Cheng, Lei; Gan, Fei; Xu, Ningge
Highlights: An independent heat extraction-release double helix energy pile is presented. An efficient numerical heat transfer model of double helix energy pile. "Effectiveness" and "saturation degree" are defined. Abstract: The application of ground source heat pump buried pipe can meet the requirements of concealment, protection and high reliability in civil air defense works, but the thermal imbalance in operation restricts the performance of system. To alleviate the problem of underground thermal imbalance, a novel independent heat extraction-release double helix energy pile was proposed, and a two-dimensional equivalent numerical model was developed and verified. Based on the numerical model, a comparison was made between independent operation of heat release and joint operation of heat release and heat extraction, and "effectiveness Ω " and "saturation degree S e " were defined as the evaluation index to research the heat extraction effects of different conditions during joint operation, the results showed that the average temperature rise in the backfill area of joint operation is 54.5% lower than that of independent operation, the heat-extracting pipe can effectively take away the heat accumulated in the energy pile area. The lower the inlet temperature of the heat-extracting pipe is, the better the heat extraction effect is. When the flow rate is about 50L/h, both the saturation degree and effectiveness are high, which has a better heat transfer effect. The larger the pipe diameter is, the greater the total heat extraction capacity of the heat-extracting pipe is, and the more favorable to the heat extraction, but the improvement effect is gradually declining, the diameter of the heat-extracting pipe is more applicable around 20 mm. For pipe length, when the effectiveness of the heat-extracting pipe is low, the length of the heat-extracting pipe can be properly reduced, which can reduce the initial cost, but when the effectiveness is close to 1, further reducing the pipe length will weaken the heat extraction of the heat-extracting pipe.